Globalisation and interdependence in the international political economy : rhetoric and reality - Jones, R. J. Barry (London ; New York : Pinter Publishers ; New York : Distributed in the USA & Canada by St. Martin's Press, 1995)
Illustrates the way in which considerations of international interdependence demonstrate the extent to which the international system is a politico-economic one. The study focuses upon interdependence and globalization, both as concepts and as central features of international relations.
Includes bibliographical references (p. [229]-241) and index.
oif 29/10/15, rpm 23/09/16
Loan
Keywords: International economic relations; International trade; Economic relations; Economy policy; World politics; Interdependence